Usability Implications of Requiring Parameters in Objects' Constructors - Stylos, J.; Clarke, S. (29th International Conference on Software Engineering (ICSE'07), 2007)
The usability of APIs is increasingly important to programmer productivity. Based on experience with usability studies of specific APIs, techniques were explored for studying the usability of design choices common to many APIs. A comparative study was performed to assess how professional programmers use APIs with required parameters in objects' constructors as opposed to parameterless "default" constructors. It was hypothesized that required parameters would create more usable and self- documenting APIs by guiding programmers toward the correct use of objects and preventing errors. However, in the study, it was found that, contrary to expectations, programmers strongly preferred and were more effective with APIs that did not require constructor parameters. Participants' behavior was analyzed using the cognitive dimensions framework, and revealing that required constructor parameters interfere with common learning strategies, causing undesirable premature commitment .